The Fama and French Five Factor Model: Evidence from an Emerging Market - Alrabadi, Hanna; Alrabadi, Dima (The Arab Journal of Administration, 2018)
This study tests the five-factor model that has recently developed by Fama and French (2015). We use daily data of 84 companies listed in Amman Stock Exchange (ASE) over the period (2011-2015). The results indicate that there is a statistically significant effect of the common risk factors, excess market return (Rm-Rf), small minus big (SMB), high minus low (HML), robust minus weak (RMW) and conservative minus aggressive (CMA) on the cross section of daily returns in ASE. However, the Fama and French five factor model fails to perfectly explain the cross section of stock returns in ASE over the study period. These results could be mainly justified by the fact that ASE is an emerging market in which many unexpected factors apart from fundamentals may interfere in affecting stock returns.